Genetic Counselling and Genetic Diseases - Waryah, Ali Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2023)
Pakistan has over 200 million people with rich ethnic diversity, showing significant social and cultural differences from the Kashmir Mountains to the shores of interior Sindh. This variation has divided the population into tribes and isolated clusters of people strongly bonded with their specific customs and trends. The familial obligations in the population have resulted in a well-differentiated cast system, having distinct genetic lineages. The social and economic influences advocate and propagate the custom of inter-family and inter-cast marriages. Consanguineous marriages are more common in Pakistan when compared to other world populations1. The global prevalence of consanguineous marriages is around 10%, whereas 73% of marriages in Pakistan are consanguineous and 80% among first cousins.